2022
DOI: 10.1186/s40644-022-00507-w
|View full text |Cite
|
Sign up to set email alerts
|

Extending the clinical capabilities of short- and long-lived positron-emitting radionuclides through high sensitivity PET/CT

Abstract: This review describes the main benefits of using long axial field of view (LAFOV) PET in clinical applications. As LAFOV PET is the latest development in PET instrumentation, many studies are ongoing that explore the potentials of these systems, which are characterized by ultra-high sensitivity. This review not only provides an overview of the published clinical applications using LAFOV PET so far, but also provides insight in clinical applications that are currently under investigation. Apart from the straigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…A similar direct comparison of the 2 systems has shown that, for shorter-lived tracers (labeled with 18 F or 68 Ga), LAFOV PET provided a liver signal-to-noise ratio equivalent to that of SAFOV PET but with an approximately 8-9 times reduction in scan duration (14). The intraindividual comparison of the 5 double-scanned patients in the present study confirms this result for a long-lived 89 Zr-labeled tracer, as the COV for a liver VOI of the 30-min SAFOV scans was in the same range as that of 3-and 5-min LAFOV scans.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A similar direct comparison of the 2 systems has shown that, for shorter-lived tracers (labeled with 18 F or 68 Ga), LAFOV PET provided a liver signal-to-noise ratio equivalent to that of SAFOV PET but with an approximately 8-9 times reduction in scan duration (14). The intraindividual comparison of the 5 double-scanned patients in the present study confirms this result for a long-lived 89 Zr-labeled tracer, as the COV for a liver VOI of the 30-min SAFOV scans was in the same range as that of 3-and 5-min LAFOV scans.…”
Section: Discussionmentioning
confidence: 84%
“…The introduction of PET/CT systems with silicon photomultipliers and time-of-flight image reconstruction capabilities already has improved the signal-to-noise ratio of PET measurements, which, in turn, has led to a reduction in scan duration or activity administration (9)(10)(11)(12). The more recent introduction of PET systems with a long axial field of view (LAFOV), with their increased sensitivity (13), further improves the signal-to-noise ratio (14,15), leading to several new opportunities in clinical practice and research (16)(17)(18). To use these new-generation of PET/CT systems efficiently, it is necessary to optimize scan protocols and understand the impact of various parameters on SUVs.…”
mentioning
confidence: 99%
“…Future studies should provide data on radiotracer dose calculation based on constructed NECR-dosage curves. Furthermore, a reduction in the required radiotracer dose will occur when advances in PET technology, such as long-axial field-of-view PET, are applied to recurrent glioma patients [60].…”
Section: Radiotracer Dosimetrymentioning
confidence: 99%
“…More recently, the next game-changing technology is the large axial field of view (LAFOV) PET/CT camera, with a substantial increase in sensitivity, hereby allowing for faster scanning and/or an important reduction in injected activity, hence radiation burden (23,24). The first LAFOV PET/CT cameras have now been installed in larger nuclear medicine departments.…”
Section: Toward a Higher Sensitivitymentioning
confidence: 99%